2011
DOI: 10.1152/ajpgi.00096.2011
|View full text |Cite
|
Sign up to set email alerts
|

Acidic bile salts modulate the squamous epithelial barrier function by modulating tight junction proteins

Abstract: Experimental models for esophageal epithelium in vitro either suffer from poor differentiation or complicated culture systems. An air-liquid interface system with normal human bronchial epithelial cells can serve as a model of esophageal-like squamous epithelial cell layers. Here, we explore the influence of bile acids on barrier function and tight junction (TJ) proteins. The cells were treated with taurocholic acid (TCA), glycocholic acid (GCA), or deoxycholic acid (DCA) at different pH values, or with pepsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…Occludin was not expressed in basal layers (Fig. 2) [12]. These findings indicate that the localization of TJs in the esophagus is different from the location of dilated intercellular spaces (DISs), which will be discussed in the following section, and which are important for determining the real barrier of the esophagus.…”
Section: Tjs In the Esophagusmentioning
confidence: 86%
See 2 more Smart Citations
“…Occludin was not expressed in basal layers (Fig. 2) [12]. These findings indicate that the localization of TJs in the esophagus is different from the location of dilated intercellular spaces (DISs), which will be discussed in the following section, and which are important for determining the real barrier of the esophagus.…”
Section: Tjs In the Esophagusmentioning
confidence: 86%
“…In evaluating the function of esophageal epithelial layers, we originally established esophageal stratified epithelial cell layers in vitro [12][13][14][15][16]. When we observed the development of stratified epithelial layers, we found that the barrier was dramatically developed 5 to 7 days after air-liquid interface (ALI)-culture of primary human squamous epithelial cells [15].…”
Section: Tjs In the Esophagusmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently established an esophageal-like stratified epithelial cell layer under ALI conditions using NHBE cells. 9,15 Although the cells were not originally from the esophagus, these cells created stratified epithelial layers, expressed cytokeratins like the esophagus, and the TJ expression pattern and gene expression pattern were similar to human esophagus. 9 Here, the stratified epithelial cell layers acquired more than 1500 O .…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Moreover, bile salts can transiently open tight junctions to improve permeability of drug molecules or nanoparticles. 27,33 Careful handling of the isolated cornea and maintenance of its physiological activity throughout an experiment is very important for reproducibility of the results. Hydration level is a parameter frequently used to evaluate damage to the cornea.…”
mentioning
confidence: 99%